Private Voluntary Organizations in Egypt - Sheila Carapico (International Institute of Islamic Thought, 1996)
Over the past five years or so, the considerable western interest in the role played by nongovernmental voluntary associations in Egypt has been reflected in a growing English-language literature on the subject. Researchers tackle the question from a range of perspectives. One approach, relatively state-centered and legalistic, focuses on how Cairo manages to control, co-opt, or "corporatize" autonomous organizations including labor and professional syndicates, agricultural and other cooperatives, and private not-for-profit groups. The principle tool for reining in private voluntary and community associations is the notorious Law 32 of 1964. Under Law 32, the Ministry of Social Affairs can interfere directly in all aspect of associational life-articulation of goals, election of officers, pursuit of projects, allocation of funds, and so on. Among the wellknown secular nonprofit groups with international linkages that have been denied licenses from the Ministry are the Egyptian Organization of Human Rights and the Arab Women's Solidarity Association. In this legal and policy milieu, many scholars and human rights activists argue that no registered association in Egypt can properly be deemed "nongovernmental." Other analysts, however, accept Cairo's position that the threat of radical Islam justifies authoritarian restrictions on independent organizations. The second group of studies is inspired partly by these concerns over the radicalization of Islamist associations. Scholars familiar with social, eco nomic, and political circumstances in the Nile Valley usually try to counteract hysterical mass media portraits of "Muslim terrorists" with inquiries into the structure, function, membership, activities, and ideologies of a range of Islamist institutions including welfare and charitable associations. The particular strength of politicized Islam in the 1990s, this research suggests, rests on the capacity of Islamist charities to provide a crucial layer of social services to a burgeoning, underemployed, increasingly impoverished population. Opinion is divided, however, on the question of whether this circumstance favors containment and stability or frustration and insurrection. A third set of studies, sometimes overlooked by scholars, comes from within the Cairo-based donor community, the "development practitioners" ...